Vocational Interests and Academic Achievement of Secondary School Students at Different Levels of Creative Thinking Ability: A Comparative Study - Mattoo, Mohammad Iqbal (INDIAN EDUCATIONAL REVIEW, 2011)
The study was carried out with an attempt to find out how a particular age group with a fibre of high creative potential are differentiable from the ones who possess low level of creative ability on certain areas of vocational interests and academic achievement. A sample of 1000 students (700 boys and 300 girls) was selected from 26 secondary schools of Kashmir valley. Baquer Mehdi’s Verbal Test of Creative Thinking Ability and Chatterji’s Non-language Preference Record were used to collect the data. Following the criteria of top 25% (Q3) and bottom 25% (Q1), two extreme groups (high and low) were identified. Two way analysis of variance was used to find out the differences between these two categories. The findings revealed that the two groups have been seen to differ significantly on variables under investigation excluding academic achievement. Besides, gender differences could not be established.